La fotografia per i beni culturali. Tecniche avanzate di trattamento digitale. Variante al metodo di creazione delle RTI. - Annunziata, Mario (Archeomatica, 2013)
The territories of the photography are many as well as the possible approaches : from pure artistic research to scientific investigation (microscopic, photogrammetric, etc). The digital image is introduced, and then led to the capillary level, the concepts of virtual simulation model. For the scope we deal with these concepts are very important and will involve two fundamental levels of the theme Cultural Heritage: the development and study. A relatively recent technique; Reflectance Transformation Imaging RTI has aroused great interest and attention in the operators of Cultural Heritage.